Dynamics of soil fertility and rice productivity in irrigated rice fields under different cropping patterns - Rufaidah Qonita Muslim; Agus Suprihatin; Anden Siti Fatimah; Waluyo Waluyo; Suparwoto Suparwoto; Jumakir Jumakir; Yustisia Yustisia; Niluh Putu Sri Ratmini; Budi Raharjo (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Irrigated rice fields serve as the primary land for rice production. Whether continuous rice cultivation or alternating with secondary crops, the cropping pattern in these filelds depends on water supply. These differences in cropping patterns will affect the soil's nutrient dynamics and rice productivity. This research aims to analyze the soil fertility dynamics and rice productivity in irrigated rice fields under different cropping patterns. The study used an oversite design with two factors, namely cropping patterns (rice-rice-rice (R-R-R), rice-rice-corn (R-R-C), and rice-rice-soybean (R-R-S)), and superior varieties (Inpari 23 and Mentik wangi). The results showed that the overall fertility of irrigated rice fields was low, with crucial limiting factors being deficiencies in total N, available P, and K nutrients. Differences in cropping patterns on Inceptisol significantly affect available P. The R-R-R cropping pattern, including the Inpari 23 and Mentik wangi varieties, provided the highest productivity, reaching 6.5-6.9 t ha-1. Selecting the right superior varieties and those by cropping patterns can increase the dry milled grain (MDG) yields by 23.52-30.1% compared to other superior varieties. Sufficient water availability throughout the growing phase can increase rice productivity by 33.3 -56.2% (1.5-2.3 times). Therefore, the key to intensive rice field management is not only to pay attention to soil fertility (nutrient dynamics), fertilization (organic and inorganic), and pest and disease control, but also to ensure the availability of sufficient water during cultivation and to use superior varieties. This research is beneficial for farmers, stakeholders, and the government in efforts to increase food security.